Cancer family caregivers' quality of life and the meaning of leisure. Issue 7 (7th September 2021) - Lim, Jinsun; Cho, Heetae; Bunds, Kyle S.; Lee, Chul-Won
Abstract: In this study, the authors examined cancer family caregivers' life experience and the meaning of leisure, focusing on their difficulties and the role of leisure. We found four main themes related to cancer family caregivers' life and leisure experiences: stressors, adapting, the need of leisure, and leisure experiences. Our results showed that the caregivers experienced high levels of psychological and physical stress and conflicts while caring for cancer patients, resulting in a poor quality of life. They believed that leisure activity is necessary and can improve their quality of life; however, they felt a sense of guilt while engaging in personal activities.